The Contrarius Actus Principle: Legal Challenges and Prospects for Reform in Executing Administrative Court Decisions - Pambudi, Lintang Ario; Hendriana, Rani; Kupita, Weda; Pati, Umi Khaerah (Universitas Negeri Semarang, 2025)
The failure to enforce state administrative court decisions with lasting legal force poses a challenge in Indonesia. Data indicates that merely 15 of 276 state administrative decisions were executed between 2013 and 2019. In 2020, statistics from the KPK, Bawas, and BPKP revealed that implementing state administrative court orders was insufficient, with an average completion rate of 34.92%. The 2021 annual report of the Ombudsman of the Republic of Indonesia documented 109 instances of non-compliance with unimplemented decisions. The research uses normative juridical methods with the addition of interviews to support existing data. This article examines the history, application, and challenges of contrarius actus, particularly in implementing state administrative court decisions. This research helps future researchers generate improvements or recommendations for state administrative court decision execution. The results show that contrarius actus originated from Roman law and is now an essential principle in state administrative law. Application of the contrarius actus in Indonesia’s administrative justice law provides for execution mechanisms without an institution or other party specialized in execution; administrative officials themselves must execute court decisions. A significant challenge in applying this principle in Indonesia is the failure of administrative officials to comply with court decisions. Despite the implementation of a merit-based system and elections aimed at selecting officials with integrity and lawfulness in filling administrative positions, many administrative officials violate court orders, making this enforcement of this concept difficult. To address this issue, it is recommended to maximize the role of the Ombudsman and state administrative courts in ensuring that administrative officials comply with legal decisions.